2020
DOI: 10.1177/0954405420937855
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relation between debinding atmosphere and mechanical properties of stereolithography-based three-dimensional printed Al2O3 ceramic

Abstract: Ceramic green bodies fabricated by stereolithography-based three-dimensional printing technology often have high loading of ultraviolet curable resins, which produce undesirable phenomena such as cracking, deformation, and blistering during the debinding process. Results showed that compared to argon and vacuum, air atmosphere provided higher flexural strength owing to the elevated density. The differences in microstructure between specimens prepared under these atmospheres were attributed to exotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The samples without impregnation in any solvents exhibited a greater flexural strength of about 138.5 MPa . This phenomenon indicated that solvent debinding tends to lead a smaller flexural strength when compared with the samples without impregnation in any solvents.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The samples without impregnation in any solvents exhibited a greater flexural strength of about 138.5 MPa . This phenomenon indicated that solvent debinding tends to lead a smaller flexural strength when compared with the samples without impregnation in any solvents.…”
Section: Resultsmentioning
confidence: 90%
“…The samples without impregnation in any solvents exhibited a greater flexural strength of about 138.5 MPa. 40 This phenomenon indicated that solvent debinding tends to lead a smaller flexural strength when compared with the samples without impregnation in any solvents. The influence factors on the flexural strength of the ceramics are complex, which may be determined by microstructures, physical properties, cracks, and other factors.…”
Section: Resultsmentioning
confidence: 96%
“…Due to the high brittleness and shrinkage of ceramics during printing and sintering, it is difficult to obtain large-dimension bioceramics. Furthermore, for application in biomedical implants, it is usually necessary to prepare internal porous architectures in the implants . Three-dimensional printing technology is an effective strategy used for the fabrication of porous architecture bioceramics. , Direct ink writing (DIW) (ink- and binder-jetting) is a classic 3D printing technique owing to its relative simplicity and compatibility with numerous materials.…”
Section: Introductionmentioning
confidence: 99%
“…is very effective to improve the usage of virgin and recycled plastics and one can easily control their viscosity and thermomechanical properties during printing. [6][7][8][9][10][11] Some studies reported on biomedical applications and thermal conductivity of PVDF highlighted that such special polymers with phase changing and chemical stability capabilities can be investigated intensely for many other aspects. 12,13 Based upon reported literature it has been observed that large-scale applications of 3D printing in construction are being explored by the researchers to reduce the cost and time of construction, its repair, and maintenance.…”
Section: Introductionmentioning
confidence: 99%